Model of Cultural Tourism at the Siak Sri Indrapura Palace Tourism Object, Riau - Bayu Seih Nanda Ria; Fajrig Arsyelan; Elvi Lastariani; Yudho Wibowo; Rangga Restu Prayogo; Muhammad Bukhori Dalimunthe (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Indonesia is one of the few countries that continues to develop the cultured tourism sector as an added value for tourists visiting Indonesia, including Riau Province which has a culture capable of attracting tourists, namely the Siak Sri Indrapura Palace. A cultural and historical tourist area that is now in the spotlight of the world community. The Siak Sri Indrapura Palace has a lot of cultural and historical heritage from Malay kingdoms in Riau and Sumatra. The heritage site of the Siak Sultanate, the largest kingdom in Riau, is also one of the other Pekanbaru historical tours most frequently visited by tourists. Historical heritage that educates people to know and introduce throughout Indonesia. Tourists visiting the Siak Sri Indrapura Palace became popular and became educational for young people and youth to remember cultural tourism, cultural heritage and motivate young people to get to know the culture of their ancestors at the Siak Sri Indrapura Palace, Riau. Culture has concrete forms (tools, architecture, clothing, crafts and others), and abstract forms (belief systems, knowledge, values and norms). If culture is associated with tourism, which in popular terms is called cultural tourism, it can be explained that cultural tourism is a type of tourism inherited from our ancestors based on traditions, arts, ceremonies and the experience of photographing a nation/tribe and its people, which reflects the diversity and identity of a society. The purpose of this research was to find out how much influence cultural tourism has on cultural motivation, cultural heritage, and intention to return to the Siak Sri Indrapura Palace, Riau. This research uses explanatory research with a quantitative approach. Questionnaires were given to tourists who visited the Siak Sri Indrapura Palace as many as 200 people with the convienance sampling technique and data analysis using path analysis. The results of the study explain that cultural tourism has a positive effect on cultural motivation, cultural heritage has a positive effect on intention to return, and cultural motivation has a positive effect on intention to return.